Conformity and Reaction to Error: An ERPs Study - Golovanova, I; Petrov, M; Bakuleva, K; Andriyanova, N (KnE Life Sciences, 2018)
This article is devoted to the analysis of cognitive indicators of conformal behavior. It presents the results of the study of EEG-correlates of conformity. The hypothesis of the study is that people who tend to the conformal behavior have a similar way of response on the errors and disagreement with the majority opinion. The experiment involved 20 participants: 11 – nonconformists, 9 – conformists according to tests (‘Interpersonal Behavior Circle’ by T. Leary and ‘Portrait Values Questionnaire’ by S. Schwartz). Participants took part in two types of tasks: arithmetic tasks and attractiveness evaluation. After solving the tasks, participants were given feedback about right/wrong decisions in arithmetic tasks, and agreement/disagreement with the majority opinion in the evaluation of people’s attractiveness. This study analyzed event-related potentials (ERPs) in the case of error or disagreement with the majority opinion. The results of the study showed the differences in the indicators of bioelectric brain activity between conformal and nonconformal participants after the disagreement with the majority opinion. Conformal participants demonstrate higher amplitude of P300 wave upon presentation of the feedback of the disagreement with the majority opinion. Thus, the conformal behavior in a situation of disagreement with others’ opinion accompanied by specific ERP patterns of the brain associated with the correction of behavior. Keywords: conformity, error processing, event-related potentials, P300, error-related negativity